(3GdBKGQ GdeJNjdI aj GdLh ef GdHNGQ GdeGFi hgi GdgGdI hGdbhS hGdTehS hGdbVHGfs - (3CHh GdNjQ MSf Hf ShGQs
(3ChdgG (B:s
(3bGd GHh GdNjQ MSf Hf ShGQ deG cGfJ LejY GdGehQ GdJi dgG Ydd heHGOF hcGfJ GdgGdI hbhS bRM hGdGKGQ GdJi JXgQ ai GdLh s
(3BNQgG (B:s
(3HYO Gf fbdg ef GddZI GdSQjGfjI Edi GddZI GdYQHjI fbdkG Hg JCOjH GdeYfi hMaXg HYhf Gddg hMSf Jhajbg heTjFJg hGdMeO ddg QH GdYGdejf hUdhGJg Ydi SjOfG eMeO GdfHi GdGei GdYQHi hBdg GdWjHjf GdWGgQjf s
(3GdfSNI HgG MhGTs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
(3QVG QGeHhQ (B(2845(4)) s
Keywords: (3GdadSaI hGdefWbs